(untitled) (Papeles, 2017)
This article aims to understand the structure of the SABER PRO exam in the writing and critical reading components from a psycholinguistic analysis. All this, in order to recognize the importance of cognitive processes developed by Colombian students which are presented in the test, whereby the 75% of them who have culminated their formative process in higher education must take.